(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2026)
Custom is considered one of the reserve sources of legislation and is the legislative basis for every new phenomenon that is not regulated by law. Custom is of two types: custom that is considered legitimate by Sharia, which is what has been accepted by jurists and scholars and does not violate public order or morals & it is considered a valid and beneficial custom that must be protected, and a corrupt custom because it regulates a habit that is associated with an activity or behavior that is considered reprehensible by society, and therefore it is reprehensible from the perspective of jurisprudential and legal rules. This research dealt with the status of customs and its impact on moral rights. Only three rights were chosen to explain the general vision of the research topic, namely (the right of authorship and copyright, the right of patent, and the right of the trade name and the rights related to the trade name - trademark, etc.) The researcher reached some important conclusions, including: - Custom, while being a reference and control for knowing the rulings for new phenomena and actions, is a broad control and reference whose applications vary, and referring to it requires knowledge of custom and the rulings for adopting and accepting it in jurisprudence and law. - Copyright, intellectual property rights, patent rights, and rights related to trade names are all financial rights recognized by Sharia and law and are entitled to legal protection due to their significant public benefit to the nation. The foundation of these rights is established and respected custom. The most important recommendations are: - The need to spread the concept of modern moral rights, the controls for their protection, the official bodies -national and international -responsible for protecting them, and the procedures and methods for requesting such protection, in order to facilitate the matter for those who request such protection, despite the development of laws in Arab countries in this field. - Spreading interest in the jurisprudence of financial transactions among law students, legal professionals in general, and those who issue fatwas and judges, due to its close connection with custom and how to know what is good and bad from it and the methods of deducing rulings on financial transactions and dealings in general. - Collecting and recording customs contributes to the development of rulings and laws, and working on recording them is considered one of the greatest works that can be done in service of the law and the people of the government.